2015
DOI: 10.1093/icvts/ivv103
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparative study of minimally invasive extracorporeal circulation versus conventional extracorporeal circulation in emergency coronary artery bypass surgery patients: a single surgeon analysis

Abstract: In our opinion, the use of MiECC in urgent CABG procedures is safe, feasible and shows no disadvantages compared with the use of CECC. Emergency operations using the MiECC system showed a significantly lower blood transfusion rate and better results concerning the unadjusted in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
1
5
0
4
Order By: Relevance
“…1. аортокоронарное шунтирование [8][9][10]; 2. протезирование аортального клапана [8,[10][11][12][13][14][15][16][17][18]; 3. пластика митрального клапана [17]; 4. реконструктивная операция на грудной и брюшной аорте [17,18]; 5. имплантация вспомогательного устройства левого желудочка (LVAD) [19]; 6. Fast Track протокол [16,20].…”
Section: показания к использованию систем Mieccunclassified
See 3 more Smart Citations
“…1. аортокоронарное шунтирование [8][9][10]; 2. протезирование аортального клапана [8,[10][11][12][13][14][15][16][17][18]; 3. пластика митрального клапана [17]; 4. реконструктивная операция на грудной и брюшной аорте [17,18]; 5. имплантация вспомогательного устройства левого желудочка (LVAD) [19]; 6. Fast Track протокол [16,20].…”
Section: показания к использованию систем Mieccunclassified
“…Использование MiECC имеет преимущество у пациентов высокого риска: старшей возрастной группы и пожилых, с сахарным диабетом, предоперационной анемией, синдромом малого сердечного выброса, предполагаемым длительным ИК и другими категориями высокого риска [10,41,43,[52][53][54].…”
Section: преимущества системunclassified
See 2 more Smart Citations
“…In order to minimize the adverse effects and improve endorgan protection minimal invasive extracorporeal circulation (MiECC) systems are successfully applied. Multiple studies have demonstrated the clinical benefits of MiECC systems, such as reduced hemodilution, reduced postoperative bleeding and transfusion requirements (3,8,9), preserved renal function (10,11), improved myocardial protection (12)(13)(14), attenuated inflammatory response (6,7), enhanced recovery of microvascular organ perfusion (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%